Predictive value of surface electrocardiogram in localizing right ventricular outflow tract premature beats: a study combining intracardiac echocardiography and electroanatomical mapping under all-zero fluoroscopy ablation - Cui, Xiaoran; Li, Ruibin; Li, Yichen; Zhang, Yi; Zhang, Jidong (Frontiers in Physiology, 2025)
ObjectiveThis study aims to evaluate how well surface electrocardiograms (ECG) predict premature ventricular contraction (PVCs) originating from the right ventricular outflow tract (RVOT) and to examine the role of intracardiac echocardiography (ICE) during their radiofrequency ablation.MethodsFrom October 2022 to December 2023, we conducted a prospective study at the Second Hospital of Hebei Medical University, enrolling 20 consecutive patients with RVOT-PVCs. In our study, utilizing ICE and the CARTO 3D electroanatomical mapping system, all procedures were performed under a completely fluoroless condition. Ablation sites were categorized into two subgroups: supra-pulmonary cusp (n = 3) and sub-pulmonary cusp (n = 17). Preoperative ECG parameters were systematically analyzed. ICE and CARTO mapping were employed to precisely localize and ablate the PVC foci, with detailed spatial electroanatomical characterization.ResultsOf the 20 patients, the origins of PVCs were found in two regions: 17 patients (85%) had PVCs originating from the sub-pulmonary cusp, while 3 patients (15%) had PVCs from the supra-pulmonary cusp. All supra-pulmonary cusp ablation targets were located in the left pulmonary cusp, 3.33 ± 0.33 mm above the cusp base. Sub-pulmonary cusp PVCs were predominantly clustered at the left anterior cusp junction (13/17, 76.5%), with one case (5.9%) at the right anterior cusp junction, averaging 2.53 ± 0.38 mm from the cusp base. Additionally, an R-wave duration ≥50 ms in lead V2 predicted sub-pulmonary cusp localization with 70.6% sensitivity and 100% specificity.ConclusionICE can clearly visualize the anatomical structures of the right ventricular outflow tract, which aids in accurately determining the ablation site. In lead V2, an R wave duration of 50 milliseconds or longer exhibits certain predictive value for ventricular premature beats originating below the pulmonary valve sinus. For PVCs originating below the pulmonary valve, the ablation target sites are primarily concentrated at the junction of the left-anterior pulmonary sinus cusp.